PHYSICAL ACTIVITY AND SCREEN TIME: A CROSS-SECTIONAL STUDY IN ALIGARH, NORTH INDIA - Sameena Ahmad; Ali Jafar Abedi; Mohammad Athar Ansari; Salman Khalil; Mohd. Najmul Aqib Khan (The Indonesian Journal of Public Health, 2021)
ABSTRACTChildren have been exposed to electronic devices. They grow up thinking that these devices are a part of their daily lives. As they get older, their dependency on such devices grows, even during school days. As a result, their physical activity is hardly handled even until they reach adulthood. This study assessed the frequency of physical activity, duration of screen time, and association between these variables amongst school children. This cross-sectional study was conducted among 800 school-based adolescents aged 12 to 14 years at A.M.U. High Schools, Aligarh, in July 2018 to June 2019. Students were asked about their physical activity and screen habits by disseminating a self- reported questionnaire. The data were analyzed in SPSS version 20.0. The study found that most of the students had adequate physical activities (75.51%), while the reported screen time duration was also adequate for most (59.1%).The association between the two variables was not statistically significant (p > 0.05). For the students with inadequate frequency of physical activity and enough duration of screen time, interventions should be done both at family and school levels to make them more physically active and better at performing studies and reaping the benefits of good health. Keywords: physical activity, school children, adolescents, screen time